The Impact of Mobile Money Services on the Financial Performance of Small and Medium Enterprises (SMEs) in Mukono Municipality, Case Study of Kikko Market - Josephine Nakigozi (Uganda Christian University, 2024)
This research aimed at finding out the impact of mobile money services on the financial performance of SMEs in Mukono municipality, a case study of Kikko market.The study was guided by four objectives namely to examine the impact of mobile money services on the financial performance of SMEs in Mukono municipality ,Kikko market, to examine the relationship between the usage of mobile money services and the financial performance indicators such as revenue,profitability,liquidity of SMEs,to identify the challenges and barriers faced by SMEs in adopting and utilizing mobile money services for financial transactions and to identify the possible solutions to the problems identified in .The study took descriptive statistics were the research design was both qualitative and quantitative data analysis techniques.The researcher used random sampling techniques for selection and purposive sampling technique for choosing SMEs that use mobile money services in Kikko market.From the results of the analysis,Findings revealed that respondents firmly believe that mobile money services have improved the efficiency and speed of transactions. It was established that the respondents firmly believe that mobile money has increased customer payments and sales and this is revealed by a mean value of 4.00, In addition, the expenses of managing and processing cash in these SMEs have decreased because of mobile money and this is revealed by the mean score of 3.86.The study found out that the average mean score, which is roughly 4.29, shows that most respondents think favorably about how mobile money services affect their company's revenue, profitability, and financial management. This indicates that most respondents believe mobile money services have improved these areas.The findings indicated that the average mean of 4.39 indicates that respondents are generally in agreement with the challenges and concerns regarding mobile money services in their business, regardless of the specific assertions.In conclusion,The study findings revealed that The financial performance of SMEs and mobile money services have a very high positive linear association and this means that SMEs' financial performance usually improves dramatically as the adoption of mobile money services rises.The study concluded that Mobile money services should be actively incorporated into SME owners' and managers' regular financial operations.